The facilitators and barriers to home-based robotic rehabilitation in India: a pilot feasibility study - Nehrujee, Aravind; Prabhakar, A. T.; Balaraman, Sathish; Bombatkar, Rasika; Prakash, Henry; Samuelkamaleshkumar, Selvaraj; Aaron, Sanjith; Bhattacharji, Suranjan; Sujatha, S.; Balasubramanian, Sivakumar (Frontiers in Stroke, 2024)
Introduction Robot-assisted rehabilitation has emerged as a promising approach for enhancing motor function in stroke survivors. However, the feasibility and effectiveness of home-based robotic training in this population are underexplored, especially in low/middle-income countries. Methods This feasibility study aimed to address this gap by examining the feasibility and effectiveness of independent home-based training using PLUTO, a robotic device for hand training. A total of 7 chronic stroke survivors were recruited, with 5 completing the study. Results The results revealed high engagement and adherence to the home-based training program, with participants averaging 1659.8 min of training over 24.8 days. The PLUTO system demonstrated excellent usability and elicited positive user perceptions. Significant improvements were observed in functional outcomes, as evidenced by a noteworthy increase in Fugl-Meyer Assessment scores (mean increase of 6.2 points, exceeding the minimal clinically important difference (MCID) of 5.35 points). Furthermore, participants showed improvements in the ABILHAND measure (mean improvement of 1.24 logits, surpassing the MCID of 0.2 logits) and the Barthel Index (mean increase of 8.8 points). Conclusion These findings demonstrate the feasibility and effectiveness of home-based robotic rehabilitation for chronic stroke survivors. This has implications for expanding access to rehabilitation services in low- and middle-income countries, enhancing patient engagement and adherence, and improving functional outcomes. Larger controlled studies are warranted to evaluate the effectiveness of home-based robotic rehabilitation programs.